SPE International Symposium and Exhibition on Formation Damage Control 2014
DOI: 10.2118/168149-ms
|View full text |Cite
|
Sign up to set email alerts
|

Complex Completion Design and Inflow Prediction Enabled by Detailed Numerical Well Modeling

Abstract: An Operator was unable to model a potential new (additional) completion of a 330 m cased hole perforated sand screen and ICDs interval in a mature high water cut well which was originally completed with a 916 m open hole stand alone sand screen and Inflow Control Devices (ICDs) section in a multidarcy sand. The potential opportunity to perforate this 330 m section presented significant potential reservoir drainage upside but could not be modelled using conventional well inflow prediction or reservoir simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Also, Byrne et al (2010 and2011) demonstrated how CFD could resolve asymmetric distribution formation damage near the well and capture the cross flow in the layered reservoir with a heterogeneous. A few years later, the same researchers developed a model for a perforated horizontal well (Byrne et al 2014). Additionally, Molina and Tyagi (2015) applied CFD on a near-well model to examine how a perforated gas well performs, looking in particular at various types of completion techniques and how these strategies might have erosive effects at the wellbore.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Byrne et al (2010 and2011) demonstrated how CFD could resolve asymmetric distribution formation damage near the well and capture the cross flow in the layered reservoir with a heterogeneous. A few years later, the same researchers developed a model for a perforated horizontal well (Byrne et al 2014). Additionally, Molina and Tyagi (2015) applied CFD on a near-well model to examine how a perforated gas well performs, looking in particular at various types of completion techniques and how these strategies might have erosive effects at the wellbore.…”
Section: Introductionmentioning
confidence: 99%
“…Byrne showed that CFD can resolve the formation damage of asymmetric distribution around the well (Byrne, et al, 2010), and can capture the cross-flow appearing among adjacent layers for a heterogeneous layered reservoir (Byrne, et al, 2011). Furthermore, a case study was published about the detailed modeling of a perforated horizontal well, offshore Australia (Byrne, et al, 2014). Moreover, Molina (2015) have used CFD for investigating the performance of a perforated gas well using a detailed near-wellbore model, focusing on different completion methods and erosive effects on the wellbore (Molina, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other methods of investigating the performance of perforated tubes involve theoretical and numerical simulation. Some studies have used CFD modelling to overcome the abovementioned difficulties for a wider range of applications (Byrne et al 2009;Sun et al 2011;Byrne et al 2014;Molina and Tyagi, 2015). Su (1996) used the commercial CFD code, FLUENT to simulate the smoothing effect of the wall inflow.…”
Section: Perforated Casingsmentioning
confidence: 99%